ANALISIS PENERAPAN GMP PADA PRODUKSI IKAN TERI NASI (Stolepherus sp.) DI PT. MARINAL INDOPRIMA, PAMEKASAN : Studi pada Produksi Ikan Teri Nasi di PT. Marinal Indoprima Pamekasan - Sudirman Sudirman; Lorine Tantalu (Pustaka Peradaban, 2025)
Anchovy (Stolephorus sp.) is a leading export commodity in Indonesia’s fisheries sector. However, the processing practices at PT. Marinal Indoprima, Pamekasan, remain largely manual and insufficiently compliant with product safety standards. This study aims to analyze the implementation level of Good Manufacturing Practice (GMP) and quality control based on Indonesian Ministry of Industry Regulation No. 75/M-Ind/Per/7/2010 at the company. A qualitative descriptive approach was employed, utilizing in-depth interviews, on-site observations, and questionnaires to evaluate the alignment of production processes with GMP criteria. Data were compared to regulatory standards through gap analysis using comparative tables. The results revealed suboptimal GMP implementation, particularly in production facility layout, wall conditions in production rooms, and employee discipline in maintaining hygiene and sanitation. Non-compliance with sanitation procedures poses potential risks to the safety of export products. The study concludes that enhancing production facilities, providing GMP training for employees, and strengthening internal monitoring systems are critical to ensuring compliance with national and international quality standards. Ikan Teri Nasi (Stolepherus sp.) merupakan komoditas ekspor andalan dalam sektor perikanan Indonesia. Proses pengolahan ikan teri nasi masih banyak menggunakan cara yang manual sehingga mengesampingkan keamanan produk. GMP (Good Manufacturing Practice) merupakan suatu pedoman untuk memastikan produk yang dihasilkan aman dan layak dikonsumsi, pedoman ini dapat diterapkan di PT. Marinal Indoprima, Pamekasan sebagai produsen yang memproduksi ikan teri nasi berkemasan dan bergerak dibidang ekspor. Tujuan penelitian ini adalah menganalisis tingkat penerapan Good Manufacturing Practice dan pengendalian kualitas mutu berdasarkan Peraturan Menteri Perindustrian Republik Indonesia Nomor: 75/M-Ind/Per/7/2010. Metode yang digunakan adalah wawancara, observasi dan kuisioner kemudian membuat tabel untuk diformasikan dengan Peraturan Menteri Perindustrian Republik Indonesia Nomor: 75/M-Ind/Per/7/2010 sesuai dengan kondisi yang ada di PT. Marinal Indoprima, Pamekasan. Hasil penelitian menunjukkan penerapan Good Manufacturing Practice masih kurang diterapkan karena beberapa variabel seperti tata letak fasilitas fasilitas, dinding dalam ruang produksi, serta kurangnya kedisiplinan tentang kebersihan dan sanitasi karyawan sebagai agen yang bersentuhan langsung dengan produk